The Effect of Cooperative Model Type of Decision Making Assisted Poster on Creative Thinking Ability on Biology Material - Novia, Alda; Anas, Nirwana; Kharuna (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2022)
This study aims to determine the effect of the poster-assisted Decision Making cooperative learning model on the creative thinking skills of students in class X Madrasah. This research is a type of quantitative research with a quasi-experimental design. The sample of this research is the students of class X IPA Madrasah Aliyah which consists of class X IPA 1 totaling 30 students as the experimental class and X IPA 2 totaling 30 students as the control class. The instrument in this research is in the form of a test in the form of essay questions with 1 item with indicators of creative thinking Fluency, Flexibility, Originality and elaboration. Analysis of creative thinking ability data using test formulas also with the help of Microsoft Excel 2010 Software. The prerequisite test proved to be normally distributed and homogeneous. The result of the test calculation is that it is worth 2.21076 and is worth 1.6973 so that it shows that it is accepted. The conclusions in this study explain that there is an effect of the poster-assisted Decision Making type cooperative learning model on biology material on the creative thinking skills of class X Madrasah students.